On Period of the Sequence of Fibonacci Polynomials Modulo - İnci Gültekin; Yasemin Taşyurdu (Discrete Dynamics in Nature and Society)
It is shown that the sequence obtained by reducing modulo coefficient and exponent of each Fibonacci polynomials term is periodic. Also if is prime, then sequences of Fibonacci polynomial are compared with Wall numbers of Fibonacci sequences according to modulo . It is found that order of cyclic group generated with matrix is equal to the period of these sequences.